HPTLC/HPLC and gravimetric methodology for the identification and quantification of gymnemic acid from gymnema sylvestre methanolic extracts - Ahmed, A.B.A.; Rao, A.S.; Rao, M.V.; Taha, R.M. (2013)
Gymnemic acid (GA), a well known anti-diabetic compound has been detected in methanol extracts of intact leaves and in vitro callus cultures derived from leaf explants of Gymnema sylvestre. Callus biomass was developed in MS medium with optimum plant growth regulators (OPGRs) of 2,4-D (1.5 mg L-1) + KN (0.5 mg L-1) under abiotic stress conditions at 45 days determined by growth curve analysis. GA detection and quantification were carried out using thin-layer chromatography (TLC), high-performance thin-layer chromatography (HPTLC), high-performance liquid chromatography (HPLC), and gravimetric techniques. GA detection peak area and their absorption spectra were evaluated through HPTLC and HPLC with the standard GA. Quantification of GA had showed the linearity, accuracy, robustness and precision by HPLC. GA content was significantly higher in gravimetric method than HPLC. All these methods were found to be simple, accurate, selective and rapid and could be successfully applied for the determination of GA. It could have potential as a pharmaceutical drug for Type 1 diabetes mellitus (IDDM) and obesity.